2017
DOI: 10.1094/cfw-62-5-0208
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Navy Bean Flour Particle Size on Carbohydrate Digestion Rate Measured in Vitro

Abstract: The consumption of navy beans (Phaseolus vulgaris L.) is associated with reduced cardiometabolic risk factors such as improved blood glucose control. Navy bean flours retain the nutritional benefits of navy beans, which are high in protein and fiber and low in fat and sugar. However, the particle size of navy bean flours can vary depending on the milling technology used. The purpose of this study was to investigate the carbohydrate digestion rate of navy bean flours with various particle sizes. Five samples ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
8
8
0
Order By: Relevance
“…We reported a similar pattern for navy bean flours in our previous study (Luhovyy et al, 2017). Raw and heattreated lentil flours followed a similar pattern in which flours of larger particle sizes had lower glucose release compared to flours of smaller particle sizes; however, the differences between the grinds were less pronounced with heat-treated flours.…”
Section: Glucose Release In Moist-heat Cooked Lentil Flours Of Varysupporting
confidence: 77%
“…We reported a similar pattern for navy bean flours in our previous study (Luhovyy et al, 2017). Raw and heattreated lentil flours followed a similar pattern in which flours of larger particle sizes had lower glucose release compared to flours of smaller particle sizes; however, the differences between the grinds were less pronounced with heat-treated flours.…”
Section: Glucose Release In Moist-heat Cooked Lentil Flours Of Varysupporting
confidence: 77%
“…Enhanced rates of starch hydrolysis were observed regardless of the degree of cooking, pointing to the importance of cell wall integrity for availability of nutrients contained within the cells. As a result, the authors concluded that “fine milled legume flour will not have the equivalent slow digestion property as cooked whole legumes.” In a recent study, Luhovyy, Hamilton, Kathirvel, and Mustafaalsaafin () conducted in vitro digestion of navy bean that had been ground to different sizes by pin milling. They showed that smaller particle size fractions had faster glucose release rates, an effect that persisted even when the fractions were “baked” as a flour–water paste.…”
Section: Pulse Millingmentioning
confidence: 99%
“…They showed that smaller particle size fractions had faster glucose release rates, an effect that persisted even when the fractions were “baked” as a flour–water paste. It is worth noting that the moisture content employed for baking of the flours was low (approximately 33% flour absorption basis) (Luhovyy et al., ).…”
Section: Pulse Millingmentioning
confidence: 99%
See 2 more Smart Citations